2012
DOI: 10.11646/zootaxa.3493.1.6
|View full text |Cite
|
Sign up to set email alerts
|

First record of the genus Discotylenchus Siddiqi, 1980 (Nematoda: Tylenchidae) from Iran, with description of one new and data on two known species

Abstract: The genus Discotylenchus is reported for the first time from Iran. Discotylenchus iranicus n. sp. is described and illustratedbased on morphological and morphometric characters. The new species is characterized by a combination of the followingmorphological features: lip region continuous and smooth, tapering to an offset prominent labial disc, lateral field withfour incisures, stylet length of 14–15μm, vulva position at 70.8–76.5 %, tail length of 81–100μm, conoid with a roundedtip and presence of males. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…To date, there have been no SEM studies on representatives of the genus Discotylenchus. During our studies on tylenchids in southwestern Iran, a tylenchid nematode population with a perioral disc was recovered, and after detailed study, it was assigned to the species formerly described as Discotylenchus iranicus Ghaemi, Pourjam, Atighi, Pedram and Karssen, 2012. Additional morphological and molecular phylogenetic studies were performed on the recovered population, and based on the newly obtained data, it was revealed that the population belongs to a new genus, belonging to the subfamily Boleodorinae, named in this present study as Discopersicus n. gen., currently a monotypic genus with D. iranicus (Ghaemi et al, 2012) n. comb.…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…To date, there have been no SEM studies on representatives of the genus Discotylenchus. During our studies on tylenchids in southwestern Iran, a tylenchid nematode population with a perioral disc was recovered, and after detailed study, it was assigned to the species formerly described as Discotylenchus iranicus Ghaemi, Pourjam, Atighi, Pedram and Karssen, 2012. Additional morphological and molecular phylogenetic studies were performed on the recovered population, and based on the newly obtained data, it was revealed that the population belongs to a new genus, belonging to the subfamily Boleodorinae, named in this present study as Discopersicus n. gen., currently a monotypic genus with D. iranicus (Ghaemi et al, 2012) n. comb.…”
mentioning
confidence: 69%
“…was recovered from soil samples collected about the rhizosphere of sugarcane (Saccharum officinarum L.) in Khouzestan province, southwestern Iran (GPS coordinates: N:32809.592, E:48833.977) during May 2012. Except slight difference in stylet length (12.0-13.5 vs 14-15 mm), no remarkable morphological or morphometric differences were observed between the recovered population and the type population described by Ghaemi et al (2012) (see Table 1). Detailed SEM studies of the new genus revealed it has oblique amphidial opening slits (Fig.…”
Section: Phylogenetic Analysesmentioning
confidence: 84%
See 2 more Smart Citations
“…Mizukubo (1993 described Filenchus discolabialis, later transferred by Siddiqi (2000) to Discotylenchus. To date, seven valid species, reported from all continents, are placed in the genus Discotylenchus: D. discretus Siddiqi, 1980 [type species], D. attenuatus Siddiqi, 1980, D. azadkashmirensis (Maqbool & Shahina, 1985) Siddiqi & Lal, 1992, D. brevicaudatus Brzeski, 1986 discolabialis (Mizukubo, 1993) Siddiqi, 2000, D. iranicus Ghaemi, Pourjam, Atighi, Pedram &Karssen, 2012, andD. longicauda (Maqbool & Shahina, 1985) Siddiqi & Lal, 1992.…”
Section: Introductionmentioning
confidence: 99%